ABCGM-BASED STUNTING PREVENTION GOVERNANCE IN BATANG DISTRICT - Yendra Erison (Yayasan Wayan Marwan Pulungan, 2024)
The aim of this research is to analyze the handling of stunting cases in Batang Regency using the ABCGM collaborative approach. Stunting cases in Batang Regency are currently still quite high. This type of research uses qualitative methods with a descriptive approach. Researchers collected data from various literature and official media that were relevant to this research. Data analysis in this research uses the Miles and Huberman approach, where in qualitative data analysis research goes through the stages of data collection, data reduction, data presentation and ending with a conclusion. The research results show that ABCGM cooperation in handling stunting cases in Batang Regency is not optimal. This is because the synergy between each actor is very limited so that communication coordination has not been developed properly. Handling stunting cases in Batang Regency is dominated by the central role of the Batang Regency Government itself. The involvement of non-government actors is still limited, even though ABCGM collaboration if carried out could speed up the handling of stunting cases in Batang Regency. ABCGM collaboration is very important because local governments are unable to handle stunting cases, which until now have been called a multidimensional problem.